Computational modelling studies of Fe-Co-M (M=Pd,V,Ti,Cr) magnetic alloys - Ledwaba, Tebogo Martina (My University, 2022)
FeCo alloys are considered attractive soft materials due to their superior properties, particularly their high saturation magnetization and mechanical strength. These systems are important in applications such as aerospace and automotive industries. However, it was reported that the B2 FeCo binary alloy shows low levels of ductility at room temperature, which makes this alloy difficult to process. Furthermore, the current application of FeCo fails to sustain high-temperature environmental conditions for a long period which poses a limitation for use in the aerospace industry. In this study, multi-scale computational methods were used to investigate the stability and possible phase transformation of binary Fe50Co50 and the ternary Fe50Co50-xMx (M = Pd, V, Ti, Cr) alloys. The ternary alloying with M impurities was conducted to enhance the ductility, workability and the transformation temperature of the binary system. Firstly, the stability of the binary Fe50Co50 and ternary Fe50Co50-xMx alloys were investigated using the density functional theory. A supercell approach has been used to add ternary elements on the Co sub-lattice of Fe50Co50 system to obtain different atomic percentage compositions. Initially, these structures were fully optimized to obtain better precision of equilibrium lattice parameters, magnetic and thermodynamic properties. It was found that the lattice constants of the binary Fe50Co50 are well in agreement with previous experimental data to within 2 %. The heats of formation was found to decrease with an increase in V, Ti and Cr compositions which suggest that the structures are thermodynamic stable. In the case of Pd addition, it was revealed that the structures are thermodynamically unstable except 6. 25 at. % Pd (heats of formation is negative). The magnetic moments decrease slightly with ternary additions. This suggests that these dopants are likely to minimally reduce the magnetism of Fe50Co50. The elastic constants revealed enhanced mechanical stability for the entire concentrations of Fe50Co50-xMx alloys due to positive 𝐶’ (𝐶’ > 0). The ductility and brittleness behavior of the B2 Fe50Co50-xMx alloys was evaluated through the three quantities: Poisson's ratio, Pugh ratio (B/G), and the Cauchy pressure at different compositions. It was revealed that doping with M effectively enhances the ductility of the binary Fe50Co50 system. Secondly, the semi-empirical embedded atom interatomic potentials method incorporated in the LAMMPS code was employed to investigate the temperature dependence on the lattice parameters of the binary Fe50Co50 and ternary Fe50Co50-xMx alloys. The lattice parameter increases as the temperature is increased, but no transformation behavior was observed. This was also confirmed from the XRD patterns. Furthermore, the melting temperature of Fe50Co50 alloy is slightly reduced from 2200 K to 1800 K. Lastly, cluster expansion (CE) and Monte-Carlo (MC) simulations were employed to determine ground-state structures, phase changes and high temperature properties of binary Fe-Co and ternary Fe-Co-M alloys. Three new ground-state stable structures were generated from Fe-Co and (FeCo2)2 is the most stable structure due to the lowest heats of formation. There are no new stable structures for FeCo1-xPdx apart from the parent phases. The cluster expansion of FeCo1-xVx generated three new ground-state systems and VFe2Co is the most thermodynamically stable phase. Furthermore, FeCo1-xTix and FeCo1-xCrx generated one (Fe8Co6Ti2) and five ground-state stable structures, respectively. (CrFe2Co)4 is the most thermodynamically stable phase with the lowest heats of formation. Phase diagrams were also constructed to indicate the mixing of the ternary Fe-Co1-xMx systems. The findings revealed that Fe-Co1-xPdx and Fe-Co1-xVx mix at similar temperatures, whereas Fe-Co1-xTix and Fe-Co1-xCrx mix at higher and lower temperatures, respectively.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2022
Keywords: FeCo alloys; Environmental conditions; Computational methods; Binary alloy; Magnetic alloys; Iron-cobalt alloys; Aerospace industries; Neural computers; Ternary alloys; Computational physics